MICROSURGICAL VARICOCELECTOMY IN PRE-PUBERTAL CHILDREN: SAFETY, EFFICACY, AND REPRODUCTIVE IMPLICATIONS - A CASE REPORT AND LITERATURE REVIEW - Bakri, Syarif; Azis, Abdul; Zainal, Ahmad Taufik Fadillah; Rahmat A., Saidah; Makkaraka, Moh Anfasa Giffari (Indonesian Journal of Urology, 2025)
Objective: In this report, we aim to present a case of a prepubertal child with left varicocele who underwent successful microsurgical ligation. Case(s) Presentation: A 9-year-old boy was admitted to urology clinic due to his parents complaint about a mass in his left scrotum. We diagnosed this patient with grade III varicocele (Dubin-Amelar classification). The patient underwent microsurgical ligation surgery. After surgery, the mass such as "bag of worms" disappeared and the testicular volume increased by 53% from preoperative volume (1.8 to 2.3 cc). Discussion: The results of this case report indicate that microsurgical ligation of varicocele in children is a safe and effective therapeutic option. Conclusion: Microsurgical ligation of varicocele in pre-pubertal children represents a safe and effective therapeutic option, offering symptom relief and potential preservation of future fertility. Further studies are warranted to elucidate the long-term outcomes and reproductive implications of microsurgical varicocelectomy in this population. Keywords: Microsurgical ligation, varicocele, children.